Elucidating Carbohydrate-Protein Interactions Using Nanoparticle-Based Approaches - Kim, Dongyoon; Rahhal, Nowras; Rademacher, Christoph (Frontiers in Chemistry, 2021)
Carbohydrates are present on every living cell and coordinate important processes such as self/non-self discrimination. They are amongst the first molecular determinants to be encountered when cellular interactions are initiated. In particular, they resemble essential molecular fingerprints such as pathogen-, danger-, and self-associated molecular patterns guiding key decision-making in cellular immunology. Therefore, a deeper understanding of how cellular receptors of the immune system recognize incoming particles, based on their carbohydrate signature and how this information is translated into a biological response, will enable us to surgically manipulate them and holds promise for novel therapies. One approach to elucidate these early recognition events of carbohydrate interactions at cellular surfaces is the use of nanoparticles coated with defined carbohydrate structures. These particles are captured by carbohydrate receptors and initiate a cellular cytokine response. In the case of endocytic receptors, the capturing enables the engulfment of exogenous particles. Thereafter, the particles are sorted and degraded during their passage in the endolysosomal pathway. Overall, these processes are dependent on the nature of the endocytic carbohydrate receptors and consequently reflect upon the carbohydrate patterns on the exogenous particle surface. This interplay is still an under-studied subject. In this review, we summarize the application of nanoparticles as a promising tool to monitor complex carbohydrate-protein interactions in a cellular context and their application in areas of biomedicine.